The Effect of Parental Involvement and Socioeconomic Status on Junior School Students’ Academic Achievement and School Behavior in China - Duan, Wenjie; Guan, Yuan; Bu, He (Frontiers in Psychology, 2018)
A survey was conducted on 19,487 Chinese junior school students to elucidate the moderating role of socioeconomic status (SES) in the relationship between parental involvement (i.e., home-based involvement and academic socialization) and junior school students’ performance in school (i.e., academic achievement and school behavior). The data includes 10,042 males and 9,445 females (mean age = 14.52, SD = 1.24). It was taken from the 2013-2014 Chinese Educational Panel Survey (CEPS), that was administrated by the National Survey Research Center at Ren-min University of China. The results demonstrate that SES negatively moderates both the relationship between academic socialization and academic achievement, and the relationship between home-based involvement and school behavior. Findings imply that parental involvement activities are highly beneficial for junior school students in families with low SES. Academic socialization is generally associated with academic success, whereas home-based involvement closely relates to school behavior. Future home-based interventions can be developed to promote parental involvement activities in low-SES families. The results also showed important implications for the development of family education in China.